Does Financial Literacy Mediate, Future Perspective, and Risk Tolerance on Retirement Saving Behavior. - Sulistianingsih, Henny; Maivalinda, Maivalinda; Srihasnita, Rita; Zetri, Rifaldo; Rismanda, Rachyta (Universitas Bangka Belitung, 2025)
This study sought to investigate how retirement saving behavior was impacted by financial literacy, future perspective, and significant risk tolerance. Additionally, the financial literacy factors mediate risk tolerance and future perspective. The causal design is a type of quantitative descriptive research that is useful for analyzing one variable's effects on another or measuring the relationship between research variables. All of the participants in this study were Padang residents. Random sampling was used as the sampling method. Primary data and Likert scale measurements were used. The data processing technique used the SEM method based on Partial Least Square (PLS.). The results of this study stated that financial literacy had a significant positive effect on retirement savings behavior. Future perspective had a significant positive effect on financial literacy and retirement savings behavior. The risk tolerance variable had a significant positive effect on financial literacy. Conversely, risk tolerance did not affect retirement savings behavior. Financial literacy as a mediating variable, future perspective, and risk tolerance did not affect their retirement savings planning.